Identifikasi Zona Potensi Air Tanah Berbasis Sistem Informasi Geografis di Kabupaten Lampung Tengah - Jati, Galih Kuncoro; Ridwan, Ridwan; Oktafri, Oktafri; Asmara, Sandi (abe.fp.unila.ac.id, 2024)
Water is an essential natural resource playing a critical role in human life. Most of the community's needs for drinking water, industry and agricultural irrigation are met from groundwater sources, with agricultural irrigation being the largest user. Central Lampung Regency is dominated by agricultural land and plantations as the main economic sector. Groundwater is a more secure, drought-resistant and easily accessible source, which greatly supports agriculture in this region. This study aims to identify groundwater potential in Central Lampung Regency using remote sensing data and Geographic Information Systems (GIS). Remote sensing applications are employed to assess vegetation density through the Normalized Difference Vegetation Index (NDVI) algorithm. This parameter is then overlaid with other factors, such as soil type, rainfall, land cover, rock lithology, aquifer productivity, slope, and the Topographic Wetness Index (TWI), resulting in a groundwater potential map. Based on the generated groundwater potential map for Central Lampung Regency, it is found that the distribution of groundwater potential is as follows: 0.03% with very high potential, 6.03% with high potential, 84.11% with moderate potential, 9.77% with low potential, and 0.06% with very low potential. Keywords: Groundwater, GIS, NDVI, Remote Sensing